DEVELOPMENT OF INTERACTIVE DIGITAL BOOKS BASED ON LECTORA INSPIRE FOR INDONESIAN LANGUAGE CLASSES - Fajri, Zaenol (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Media is very important in delivering learning material to media students that can be used such as interactive media, books and the internet. Along with the development of the times and increasingly advanced technology, the development of books and interactive media is very suitable to be developed by the applicable curriculum. The purpose of this study is to produce Interactive Digital Books Based on Lectora Inspire in Research Methods Subjects that are developed according to the elements of validity, effectiveness, practicality, and attractiveness. This study uses a 4-D development model developed by Tiagarajan and Sammel (1974), namely (1) Define, (2) Design, (3) Develop and (4) Disseminate. The results of this study, the average validity reached 86.5% (very valid). The effectiveness is 88.5% (very effective), and the effectiveness of learning outcomes is 90,7% (Graduated), the practicality of the product reaches 91.8% (very good) and the attractiveness of the product reaches 94.2% (very interesting). The conclusion from the results of this study, Interactive Digital Book Based on Lectora Inspire in Research Methods Subjects can be used by lecturers and students as a practical learning resource and effectively improves student learning outcomes.